Manajemen Modal Kerja, Piutang, Dan Profitabilitas Dalam Masa Pandemi Covid-19 (Studi Pada PT. Benny Surabaya Trans) - Musdalifah Musdalifah; Purnamawati Purnamawati (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The purpose of this study wa to determine the conditions of working capital, accpunts receivable, and profitability management at PT. Benny Surabaya Trans. The subjects used in this study were companies engaged in shipping services throughout Indonesia, namely PT. Benny Surabaya Trans. The object of this research is to analyze working capital management, accounts receivable management, profitability management during the Covid-19 pandemic. The type of research is descriptive quantitative. The calculation of wprking capital turonover accurs as a result of instability due to descreasing current liabilities so that it is not effective for working capital. The receivable turnover calculation id accordance with the company standard which is set twice a mont for receivables turnover so that it is effective and runs well. The calculation of return on assets is volatile due to increases and decreases in net income which are not considered by rhe manager so that it is ineffective, which means that profitability management is also closely relates to working capital management and receivables management.